Giving and receiving written feedback on research reports: a narrative review and guidance for supervisors and students (Health Education in Practice: Journal of Research for Professional Learning, 2020)
PurposeWritten feedback on research-related writing is an important educational component of novice researcher development. Limited evidence exists to inform effective written feedback, particularly in relation to research reports by novice researchers. The aim of this narrative literature review was to explore supervisor and novice researcher perspectives on the provision of written feedback, particularly in the context of their evolving supervisory relationship. MethodsA systematic search of peer-reviewed journals in educational and health databases was undertaken for the terms ‘written feedback’ and ‘research report’, from January 2001 to August 2020. Identified literature was critiqued for methodological quality. Findings were coded, grouped and described as themes. Next, the themes and their parts were applied to the development of a two-part written feedback checklist that includes separate but related recommendations for supervisors and novice researchers.FindingsFrom 35 included papers, the four main themes that related to written feedback on research reports by novice researchers were: the emotional impact of receiving or giving written feedback; written feedback in the supervisory power dynamic; communicating written feedback; and the content and structure of written feedback. The changing nature and complexity of factors associated with written feedback from research supervisors reflected the transition from a supervisory relationship to a peer relationship. The checklist developed from the synthesised data is intended to provide guidance for supervisors and students about their respective and shared responsibilities within a supervisory relationship.  ImplicationsIncreased awareness of the characteristics, roles and impact of written feedback will assist supervisors of novice researchers to provide effective written feedback, and for students to effectively utilise written feedback. Progression of written feedback throughout the supervisory period is proposed as a means of transitioning from a teacher-student to a peer researcher relationship.